Development of a Health Index for Transformer Condition Assessment Using an Online Dashboard - Sripatawasumadee, Kornchet; Maneerat, Noppadol; Dechothamsathit, Vorawut; Kingkham, Sukanya; Jeenmuang, Siwakorn; Pattanadech, Norasage (My University, 2025)
Power transformers are critical components in electrical power systems in the transmission and distribution of electricity. Keeping them in good working condition is necessary to prevent power outages and ensure system stability. Traditional maintenance strategies, such as time-based maintenance, may not always be the best way to avoid problems or use resources efficiently. To improve this, the concept of a Health Index (HI) has been introduced as a systematic method for transformer condition assessment. By integrating various diagnostic data - such as load data, oil analysis, maintenance record, and on-load tap changer (OLTC) parts - into a unified HI score, asset managers can make informed decisions regarding maintenance prioritization and replacement planning. Furthermore, this paper proposes the development of an online dashboard system that facilitates the input, storage, and visualization of transformer health data. This user-friendly platform enables engineers to monitor condition trends in real time and supports strategic maintenance scheduling. The integration of Health Index evaluation with an accessible digital interface enhances the efficiency, transparency, and reliability of transformer asset management practices.
Keywords: condition assessment; dashboard; health index; power transformer